Substitution between managers and subordinates: evidence from British football - Sue Bridgewater; Lawrence M. Kahn; Amanda H. Goodall (Institute for the Study of Labor (IZA), 2009)
We use data on British football managers and teams over the 1994-2007 period to study substitution and complementarity between leaders and subordinates. We find for the Premier League (the highest level of competition) that, other things being equal, managers who themselves played at a higher level raise the productivity of less-skilled teams by more than that of highly skilled teams. This is consistent with the hypothesis that one function of a top manager is to communicate to subordinates the skills needed to succeed, since less skilled players have more to learn. We also find that managers with more accumulated professional managing experience raise the productivity of talented players by more than that of less-talented players. This is consistent with the hypothesis that a further function of successful managers in high-performance workplaces is to manage the egos of elite workers. Such a function is likely more important the more accomplished the workers are - as indicated, in our data, by teams with greater payrolls.
Keywords: J24; M51; 330; Productivity; leadership; Führungskräfte; Personalführung; Fußballsport; Professioneller Sport; Substitutionseffekt; Produktivität; Großbritannien